The Influence of Using 3D Holographic Mediaon Student Engagement in Learning Geometry (International Journal of Scientific Research and Management (IJSRM), 2023)
This study aimed to investigate the influence of using 3D holographic media on students’ learning engagement in geometry. The research design employed both quantitative and qualitative approaches with a sequential explanatory method. The research subjects were eighth-grade junior high school students. Data collection instruments included interviews and observation sheets. The data analysis technique used normative analysis. The results of this study suggest that the utilization 3D holographic media has a positive impact on students’ engagement in geometry learning. The summary of observational outcomes reveals a continuous rise in student activity, indicating their adjustment to the learning process. These results corroborate the idea that 3D holographic media improves student interactivity and engagement, consistent with findings from prior research. Despite the improvements, the study underscores potential areas for further enhancement, especially concerning group collaboration